EFFECTIVENESS ANALYSIS OF WATERFALL AND AGILE PROJECT MANAGEMENT METHODOLOGIES – A CASE STUDY FROM MACAU'S CONSTRUCTION INDUSTRY - Marques, Joao Alexandre Lobo; Morais, João José Bragança dos Reis; Alves, José; Gonçalves, Marcus (Revista Gestão em Análise, 2023)
The adoption of project management techniques is a crucial decision for corporate governance in construction companies since the management of areas such as risk, cost, and communications is essential for the success or failure of an endeavor. Nevertheless, different frameworks based on traditional or agile methodologies are available with several approaches, which may create several ways to manage projects. The primary purpose of this work is to investigate the adequate project management methodology for the construction industry from a general perspective and consider a case study from Macau. The methodology considered semi-structured interviews and a survey comparing international and local project managers from the construction industry. The interviews indicate that most construction project managers still follow empirical methods with no specific methodology but consider the adoption of traditional waterfall approaches. In contrast, according to the survey, most project managers and construction managers agree that the project's efficacy needs to increase, namely in planning, waste minimization, communication increase, and focus on the Client's feedback. In addition, there seems to be a clear indication that agile methodology could be implemented in several types of projects, including hospitality development projects. A hybrid development approach based on the Waterfall and Agile methodologies as a tool for the project management area may provide a more suitable methodology for project managers to follow.
Keywords: PMBOK; agile; construction industry; project management methodologies

The Emergence of Resources Seeking Chinese Firms’ Specific Advantages in Emerging Market - Ojo, Olukayode Iwaloye; Im, Hong Kei; Adeniyi, Damilola Olarewaju; Gbadamosi, Ayantunji; Alves, Jose; Link to external site, this link will open in a new window; Trimarchi, Michael (Sustainability, 2022)
It is argued that the role of the Chinese government to support the cross-border operations of Chinese firms is to assist these firms in overcoming their limited established brands, and their disadvantages in technology and managerial resources, which were also the reasons why such firms decided to enter emerging markets instead of developed markets. This strategic choice is preferred to avoid direct confrontation with established firms from developed countries endowed with superior ownership advantages. Therefore, Chinese resources seeking firms innovate by increasing investment in developing and emerging markets to develop unique ownership advantages for sustainable market development and competitive advantage. This research investigates the ownership advantages of resources seeking Chinese firms in these markets using the OLI theory. The paper contributes to explaining the specific advantages of Chinese MNEs when entering emerging markets. The study applied a two-stage qualitative methodology to examine Chinese firms operating in Nigeria. The first stage included an exploratory study based on interviews with key informants and experts while the second stage included a case study methodology. The study focused on resources seeking Chinese MNEs operating in Nigeria.
Keywords: OLI theory and Chinese firms; emerging markets; ownership advantages; resources seeking MNEs

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny O. L. (USJ Theses and Dissertations, 2022)
Macao is well known for its gaming industry. However, there are also many traditional small-to-medium enterprises which are family-owned and run. There is no doubt that social capital is one of the key competitive advantages that family businesses possess, particularly when it comes to Chinese businesses with strong family values that emphasize the importance of trustworthiness and guanxi (relationships). As opposed to other forms of capital, social capital cannot be passed from one generation to another through the will of the incumbents. So, how is social capital passed on in family businesses from one generation to the next? Based on an in-depth study of five cases of successful family businesses in Macao, this research identified the forms of social capital present in business families and the succession process of these firms. From the generalizations drawn from the five cases, a theoretical framework is proposed to understand the intergenerational transmission of social capital in Chinese family businesses
Keywords: China Macau (Special Administrative Region); Family-owned business enterprises

Transgenerational Entrepreneurship In Chinese Family Businesses: Proposal For A Model Of Work-Life Synergy - Phillips, Jenny O. L.; Osorio, Arturo E.; Alves, José (2018)
Family business are the dominant form of business in the world, and Chinese family business (CFB) is a unique type of family business that relies on collective action to survive. This paper argues that in CFBs, entrepreneurial actions are transgenerational collective endeavors, and successors are groomed as stewards of the family legacy. Work-life relationship in CFBs is about synergy and not balance because the family identity is the business identity, and vice-versa. Using five in-depth case studies, this research introduces an alternative understanding of CFBs and proposes a model of work-life synergy in transgenerational entrepreneurship based on discussion of five theory-based propositions. This model explains that through emphasizing on the business family's shared value and entrepreneurial legacy, elements of trust, shared identity and stewardship of family members are enhanced which leads to collective action and goal of the business family, resulting in transgenerational entrepreneurship. Limitations and future research are presented.
Keywords: Chinese family business; family legacy; stewardship; transgenerational entrepreneurship; work-life synergy.

Shopping styles of Chinese generation Y: luxury shopping in Macau - Chan Sai Lai (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A comparative analysis of smartphone brands in Macau: Apple and Samsung - Cheong, Ka Man (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring service quality in luxury retail in Macau - Mui, Wing Yan (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny Oliveros Lao (University of Saint Joseph, 2018)
This dissertation reports on a study which aims to add to the theoretical understanding of how social capital is transferred from one generation to the next in business families. Studies in the field of family business have emphasized the importance of succession for the survival of family businesses, but while the succession process and planning have been widely studied, the examination of social capital succession is scarce. As for the studies in family business’s social capital, the importance of social capital as a source of competitive advantage which already exists in business families have often been expressed, but there is a lack of research in the means of transferring this form of capital from the family business leaders to their successors. The study presented here addresses this gap in family business succession literature and social capital literature, explaining the means of transgenerational succession of social capital in family businesses. This is a qualitative research using the multiple case study method which aims to investigate the means of social capital transmission by comparing the cases of five different Chinese family businesses in Macau, which are in the succession process, with the successor currently managing the firm while the former generation business leaders are in the process of handing over the business and preparing for retirement. In doing so, this research offers a theoretical framework of explaining how social capital is transmitted from the incumbents to the successors throughout a five-stage succession process developed for this research. The forms of social capital that exists in family businesses are identified from previous literature, in order to clearly explain how these different forms of social capital are passed on from generation to generation based on the review on succession process introduced in published literature. A theoretical iii framework is formed from the two parent theories on family business succession and social capital, and is then verified empirically from five Chinese family businesses in Macau. The cases are developed through in-depth interviews with the incumbents and successors of the family businesses, informal interviews with stakeholders (including family members, business associates, non-family employees and customers), direct observation on the premises of the Chinese family businesses and secondary data, in order to study the process of intergenerational transmission of social capital in these Chinese family businesses
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Early career promotions in hospitality - Phinn, Kan Yean (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Lusophone-African multinational enterprises internationalization mode: a case analysis of Angolan and Mozambican enterprises - Gonçalves, Marcus Vinicius Amaral (University of Saint Joseph, 2017)
Several internationalization theories have been developed over the past few decades that have made great contributions in explaining enterprise internationalization and their mode of entry strategy. It has been suggested that the determinants of entry mode choice of enterprises from emerging and frontier markets differ from those of comparable enterprises from advanced economies. Literature review appears to indicate that there is a need to expand the framework for entry mode strategies to accommodate the expansion issues enterprises from emerging and frontier countries face in the global marketplace. Nevertheless, not much information and acceptable conclusion has been made on how MNEs from frontier markets internationalize and what factors influence their choice of entry into those markets. This study investigated the internationalization strategies of Lusophone Africa MNEs from Angola and Mozambique, more specifically their entry mode. Information was gathered through a survey of 29 MNE’s upper management respondents and subsequent face-to-face semi-structured interviews with 24 of them in their countries. The results of this study suggest that most MNEs opted for equity-based investment strategies, mainly joint venture and M&E as their preferred mode of entry when internationalizing. A significant group of them opted for e- commerce/e-business strategies, and direct and indirect exports. A smaller portion of the interviewees chose Greenfield investment as a mode of entry. Many of these MNEs could be classified as born global/INV. Finally, this study presents a conceptual framework for use in studying the entry mode choice of enterprises from Lusophone Africa frontier markets and presents research propositions for better understanding the determinants of entry mode strategies of enterprise from Angola and Mozambique. Keywords: Internationalization, Entry Mode, Emerging Markets, Frontier Markets, Lusophone African MNEs, Angola, Mozambique
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Investigating the relationship between the human resource management practices and the "intention to stay"of therapists in Macau - Hoi, Mang Hong (University of Saint Joseph, 2017)
Keywords: 2017; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Citizens' satisfaction with the services delivered by IACM-HAWKER Management Services - Hong, Mei On (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Can the application of neuroscience improve processes for ongoing improvement in organizations? - Alves, José (University of Saint Joseph, 2016)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Career aspirations of generation y: the case of event management graduates in macau - Alves, José (University of Saint Joseph, 2016)
Keywords: China Macau; Marketing; Organizational effectiveness; Planning; Special events; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of Business Clusters in Macau - Alves, Jose; Trimarchi, Michael (University of Saint Joseph, 2016)

Meetings and conventions in Macao: Challenges and opportunities - Che, Sio Wang (University of Saint Joseph, 2016)
Keywords: Challenges; Macau; Meetings; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Feasibility study of a digital gourmet marketplace in Hong Kong - Farinha, João Pedro (University of Saint Joseph, 2016)
Keywords: Google; Hong Kong; Marketplaces; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The challenges of ethnic foodservices business in Macau: an Indian restaurant case study - Khan, Muhammad Imran (2016)
Keywords: Food service management; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study of Chinese rituals in street shops in Macau - Moreira, Irene Mitsiko Sadoyama (University of Saint Joseph, 2016)
Keywords: Business ethics; China; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Macau's Strategies to Develop Training of Talented People with Expertise in the Cooperation between China and Portuguese Speaking Countries - Alves, Jose (University of Saint Joseph, 2015)

Financial challenges of small medium emterprises in China - Fok, Gerald (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study on perceptions of young adults about speed dating service in Macao - Kuong, Weng Man (University of Saint Joseph, 2015)
Keywords: Dating services; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Young adults

Macau consumers' attitudes toward mobile advertising - Wong, Iok Fong (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Relationship marketing in retail banking in Macau - Wong, Kuai Leong (University of Saint Joseph, 2015)
Keywords: Bank management; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management style change in Laos - Xian, Jia Xing (University of Saint Joseph, 2015)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Attractiveness of Macau International Airport to AirAsia - Au, Hoi Yee (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A business plan for super baby restaurant - Chao, Pek Chu (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Going green in Sands Cotai Central Macau - Chao, Wai Chong (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Feasibility Analysis For an Academic Incubator at USJ - Cheong, Ieng (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Chew Store: a business plan - Ieong, Hio Na (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Performance management in the public sector: the case of Macau - Lai, Pou San (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Business plan for a Franchised Kumon Center - Loi, Pou Lin (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Video Content Marketing in the Retail Sector: Implementation for Macau - Lourenço, Joana (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Employee turnover and retention in hospitality industry: an exploratory study in Macau - Nantes, Belinda Fatima (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Financial flows and currency exchange in Mainland China in the foreign investor perspective - Rodrigues, Nuno Miguel Vieira (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The supply chain analysis of Kuong Kei Logistics - Sou, Tak Keong (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study on the turnover of direct sellers in Macao: the case of NuSkin Macao - Tang, Weng In (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Key success factors of the small and medium-sized enterprises (SMES) in Macao - Wong, Sio Kuan (University of Saint Joseph, 2014)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

E-waste recycle plant in Macau: a feasibility study - Chan, Kuai Son (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Web portals in Macau: qoos.com versus cyberctm.com - Cheang, Melody (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Real estate transactions in Macau: issues and recommendations - Cheong, Kong Nam (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Employee turnover after company merger: A case in Macao - Cheong, Lien Hon (University of Saint Joseph, 2013)
Keywords: Employees; Theses and Dissertations Master of Business Administration (MBA); Turnover; University of Saint Joseph

Study on management style changes in Mongolia - Fong, Mei Lei (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business operations improvement at the Kin Fu Chinese restaurant - Fong, Seng Lok (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The green consumer target market and its most effective marketing mix - Guy, Wendy Danielle (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of Fuhong Society's marketing strategies to achieve self-sustainability - Karki, Sanjib (University of Saint Joseph, 2013)
Keywords: Fuhong Society; Marketing Management; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business analysis and development of a tutorial center in Macau - Lai, Kai Neng (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The labor market for casino dealers in Macau: future scenarios and implications for the city of dream - Lam, Ka Fai (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Macau lodging sector: current needs and opportunities for budget hotels - Lei, Kuong Chon (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Sai Van Lake square integrated tourism project: issues and reflections - Lei, Lai Leng (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Training busy middle-level managers: an exploratory study in Macao hotel industry - Leng, Chiang (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Analysis of customer in-store experience at the atrium Macau - Leong, Ka Wai (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan of waffle crepe delight - Leong, Weng Man (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Dutch Disease In Macau: Theoretical Modeling, Empirical Diagnosis And Treatments - Mieiro, Susana Margarida Baptista (University of Saint Joseph, 2013)
Keywords: Dutch Disease; Macau

Training and development at the grand LapA hotel in Macau: a qualitative study - Ng, Choi Teng (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploring fashion trends with internet blogs: an application to Design Esta Studio - Ng, Ian Io (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

What Motivates Generation Y Employees in Macau: An Exploratory Study - Organo, Olen Royce Riesgo (University of Saint Joseph, 2013)
Keywords: Employee motivation; Macau; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan for a cultural - Fashion retailer - Pereira, Alexandre Eduardo (University of Saint Joseph, 2013)
Keywords: Fashion; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Subjective Wellbeing And Quality of Work Life in Macau - Rato, Ricardo Jorge Parreira (University of Saint Joseph, 2013)
Keywords: China; Macau (Special Administrative Region); Quality of life; Research

Housing (un) affordability in Macau - Tang, Mui Wa (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Animal welfare in Macau: a feasibility study for a nonprofit organization - Vong, Sok I. (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Molecular cuisine in Macao - Wong, Un (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Social enterprise business plan: "green idea" - plastic recycling industry - Chan, Man Leng (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Employee engagement at the BMW Concessionaires (Macau) Ltd - Gabriel, Eurico (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

"Going through the mist": early career transitions of Chinese Millennial returnees - Porschitz, Emily T.; Guo, Chun; Alves, José (Managing the New Workforce, 2012)

A financial valuation study of oracle corportion - dissertation - Zhao, Wen Yuan (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Accounting in Macau: A Historical Perspective from 1970s until 2008 - Lam, Ching Chi (University of Saint Joseph, 2011)
The current research study embraced the objectives to investigate the transformation of accounting in Macau from the first set of accounting legislations in 1970s, through the first set of accounting standards in 1983, until a year after the first application of international accounting standards, by 2008. From the transformation, the role taken by accounting in the economy and the factors that have influenced the transformation were intended to identify. Through the historical picture, findings have supported and expanded the theoretical concepts that accounting was taking both active and passive roles in the economy. Furthermore, they also supported the theoretical concepts that culture, economic environment, political environment and education influenced the transformation of accounting. The objectives have been structured through three research issues identified from the analysis of past literatures. Five qualitative and quantitative research studies have been carried out, using primary and secondary data from both primary and secondary sources. In-depth interviews on 13 representative respondents of the government, the profession, the industry and the academia, directly or in-directly related with accounting have been done. A case study on a company doing business in Macau since 1970s was included to enrich, supplement and evaluate the findings on the accounting practice of Macau. Based on the findings, a model has been constructed that represented the interaction between accounting and the different factors of the economy. Contributions from the research findings have enriched the research literatures on the area of accounting history. Implications from the findings have generated better insights for the business and economic histories of Macau
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; Thesis and Dissertations PhD in Business Administration (D-BA); University of Saint Joseph

The pay structure reform of Macau civil service: the civil servants' perspective - Leong, Vengian (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Service quality in the public sector: an exploration in Macao's public service and information center - Sio Lameiras, Nga Man Maria (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Foreign workers in Macau - Wong, Kit Weng (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Assessment of the factors affecting solid waste management in Macau - Amuno, Solomon (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Retention factors for I.T. professionals in Macao - Lei, Sok Chi (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Governance of urban planning in Macau - Leong, Fong Peng (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

(Em)powering Timor-Leste: the electricity sector reform - Mineiro, Rui (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph